Analisis Strategi Komunikasi Komdigi Dalam Memerangi Judi Online - Sergie Loudryana Febrianto (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the digital communication strategy implemented by the Ministry of Communication and Digital (Komdigi) in combating online gambling practices in Indonesia. The research employs a qualitative method, collecting data through in-depth interviews with key and supporting informants, as well as observation of Komdigi’s official communication channels. The findings reveal that Komdigi adopts two main approaches: proactive and reactive strategies. The proactive strategy includes performance publication, special events, cross-sector collaboration, and media agenda setting. Meanwhile, the reactive strategy covers digital law enforcement, empathetic engagement with victims, and investigation of public reports. The study also finds that the #JudiPastiRugi campaign serves as a key implementation, involving cooperation with digital companies, state institutions, law enforcement agencies, NGOs, and community groups. Supporting factors for the strategy include leadership commitment, technological resources, and collaborative networks. However, challenges include content approval bureaucracy, the rapid re-emergence of gambling domains, and public perceptions of enforcement effectiveness. Observations indicate that Komdigi’s digital communication strategy is relatively effective in raising public awareness, although innovation is needed to maintain message relevance and expand campaign reach in the future.